AB0371 Is Switching from IV To SC Abatacept Therapy Sustainable in The Real World? 1-Year Analysis of The Prospective, International Action Study. (15th July 2016) - Alten, R.; Nüßlein, H.; Galeazzi, M.; Lorenz, H.M.; Mariette, X.; Cantagrel, A.; Chartier, M.; Elbez, Y.; Rauch, C.; Le Bars, M.
Abstract : Background: Open-label clinical trials have shown that patients with RA can switch from IV to SC abatacept therapy with no efficacy loss or safety concerns; 1, 2 however, findings from single-centre, real-world studies are unclear. 3, 4 Objectives: To examine characteristics at baseline and before switching, and reasons for switching, in patients who switched from IV to SC abatacept in the real-world ACTION study. Methods: ACTION is a 2-year, prospective, observational study of patients with moderate-to-severe RA who initiated IV abatacept across Europe and Canada. Enrolment periods: May 2008–Dec 2010 (biologic naïve or failed prior biologics); Sept 2010–Dec 2013 (biologic naïve); Oct 2011–Dec 2013 (failed prior biologics). This was an interim analysis of 1-year data. Assessments: baseline characteristics; reasons for switching; efficacy at the time of switch measured by EULAR response, DAS28 (ESR), DAS28 (CRP), CDAI and SDAI. Results: 2364 patients were enrolled and 2350 were evaluable. A total of 91 patients (3.9%) switched from IV to SC abatacept during their first study year: 19 were biologic naïve and 72 had failed prior biologics at study entry. Compared with non-switchers, the switch group had numerically higher percentages of patients with BMI ≥35 kg/m 2, ≥1 co-morbidity and ≥2 prior anti-TNF failures, and lower mean disease activity, at baseline. Most patients (62.6%) who switched did so after >6 months in the study (Figure ). Reasons for switching from IV to SC abatacept were available for 86 patients (94.5%; some patients had >1 reason): patient wish (53.5%), physician's preference (24.4%), safety (9.3%), poor compliance (4.7%), efficacy (2.3%), remission (2.3%), surgery (1.2%) and other (16.3%). Only 3/91 (3.3%) patients re-switched to IV abatacept; reasons were: patient wish, safety, efficacy (1 patient each). Prior to switching to SC abatacept, 64% of patients had a good/moderate EULAR response. According to mean (SD) values, disease activity before switching was moderate: DAS28 (ESR) 3.85 (1.09), DAS28 (CRP) 3.46 (1.07), CDAI 12.49 (7.70) and SDAI 13.6 (8.13). Conclusions: Few patients switched from IV to SC abatacept and most who did so switched after >6 months allowing them to first achieve stable disease activity. Switching from IV to SC abatacept was primarily driven by patient or physician preference for the SC formulation. The very low rate of return to IV (3.3%) suggests that switching from IV to SC abatacept had no adverse clinical impact. References: Keystone EC, et al. Ann Rheum Dis 2012;71:857–61. Mueller R, et al. Arthritis Rheumatol 2015;67(Suppl. 10):651–52. [Abstract 449] Reggia R, et al. J Rheumatol 2015;42:193–5. Monti S, et al. J Rheumatol 2015;42:1993–4. Disclosure of Interest: R. Alten Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, H. Nüßlein Consultant for: Bristol-Myers Squibb, AbbVie, Celgene, Chugai, UCB, Pfizer, MSD, Novartis, Roche, Speakers bureau: Bristol-Myers Squibb, AbbVie, Celgene, Chugai, UCB, Pfizer, MSD, Novartis, Roche, M. Galeazzi: None declared, H. M. Lorenz Consultant for: AbbVie, Bristol-Myers Squibb, Roche-Chugai, UCB, MSD, GSK, Sobi, Medac, Novartis, Janssen-Cilag, AstraZeneca, Pfizer, Actelion, Speakers bureau: AbbVie, Bristol-Myers Squibb, Roche-Chugai, UCB, MSD, GSK, Sobi, Medac, Novartis, Janssen-Cilag, AstraZeneca, Pfizer, Actelion, X. Mariette Grant/research support from: Biogen, GSK, Pfizer, Speakers bureau: Bristol-Myers Squibb, GSK, Pfizer, sanofi, UCB, A. Cantagrel Grant/research support from: UCB, Pfizer, Consultant for: AbbVie, Bristol-Myers Squibb, Chugai, Lilly, MSD, Novartis, Pfizer, Roche, M. Chartier Consultant for: Bristol-Myers Squibb, Y. Elbez Employee of: Bristol-Myers Squibb, C. Rauch Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Le Bars Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb